Impaired translation of CCAAT/enhancer binding protein a mRNA in bronchial smooth muscle cells of asthmatic patients - BORGER, Peter; MIGLINO, Nicola; BARAKET, Melissa; BLACK, Judith L; TAMM, Michael; ROTH, Michael (Journal of allergy and clinical immunology, 2009)
Background Bronchial smooth muscle (BSM) cells of asthmatic patients have an impaired expression of CCAAT/enhancer binding protein (C/EBP) α, which is associated with increased proliferation. Objective We sought to assess the translational regulation ofCEBPAmRNA in cultured BSM cells of healthy control subjects (n = 11) and asthmatic patients (n = 12). Methods Translation efficiency was studied by using a translation control reporter system driven by the control elements present in theCEBPAmRNA. Translation efficiency was determined by the ratio of 2 artificial hemagglutinin (HA.11) proteins: p23 and p12. We also analyzed levels of proteins that control translation ofCEBPAmRNA, namely heterogeneous nuclear ribonucleoprotein E2, calreticulin, eukaryotic translation initiation factor (eIF4E), and 4E binding protein. Results Compared with healthy control subjects, BSM cells of asthmatic patients proliferate faster (2.1-fold) and are primed for IL-6 secretion. Real-time RT-PCR showed that BSM cells of asthmatic patients express normal levels ofCEBPAmRNA, whereas they express lower levels of C/EBPα (p42). Transient transfections with the translation control reporter system construct showed a disturbed p12/p23 ratio in BSM cells of asthmatic patients relative to healthy control subjects, which coincided with lower levels of eIF4E. Conclusion BSM cells of asthmatic patients have normal levels ofCEBPAmRNA but inadequately reinitiate the translation into C/EBPα. Impaired translation control upstream of eIF4E might underlie the observed increased proliferation and priming of BSM cells of asthmatic patients.